Thermodynamic analysis of the CO2 methanation reaction with in situ water removal for biogas upgrading - Ana Catarina Faria (2018)
This study assessed, from the thermodynamic point of view, the feasibility of methane production using CO2 present in raw biogas. The thermodynamic analysis of the Sabatier reaction was performed using the Aspen Plus software and considering in situ water removal to displace the reaction equilibrium. The temperature and pressure were varied between 200 - 450°C and 1 - 30 atm respectively, the typical operation ranges of industrial catalysts. The CH4/CO2 molar ratio in the feed stream was also varied to evaluate the influence of biogas composition on methane yield and selectivity. Two types of multifunctional reactors could be considered depending on the value of the water removal fraction (R): a membrane reactor for 0<R<0.99 and a sorption-enhanced reactor for R0.99. Their performance was compared to that obtained with a traditional reactor, i.e. without water removal (R=0). Water removal increases the CH4 yield but only up to an optimum R; above this value, coke formation is favoured. This optimum value depends on the temperature, pressure, CH4/CO2 ratio and was always below 0.99. The highest improvements on CH4 yield were achieved for the lowest CH4/CO2 ratio considered. Water removal can be also particularly useful to minimize the production of COx allowing to comply with the biogas quality specifications for injection into the natural gas grid.